Impact of tranexamic acid on coagulation parameters in patients undergoing total knee replacement surgeries under tourniquet: an observational study - Singh, Ajit Kumar; Narula, Gagan Kumar; Nambiar, Bala Chandran; Bedi, Parvinder Singh; S., Deeparani; Rajkhowa, Moloy (International Journal of Research in Medical Sciences, 2018)
Background: A growing body of evidence has shown Tranexamic Acid (TXA) is effective in decreasing perioperative blood loss and transfusion requirements in both primary and revision joint arthroplasty. TXA is a synthetic drug which limits blood loss through inhibition of fibrinolysis and clot degradation. It helps reduce requirement of colloids and crystalloids and hence provides better haemodynamic stability. The aim of this study was to detect the effect of tranexamic acid on coagulation parameters and effect on bleeding in knee replacement surgeries performed under tourniquet. Methods: Patients undergone surgeries of Total Knee Replacement (TKR) performed under tourniquet were included in the study. A single dosage of 20 mg/kg per body weight of tranexamic acid was administered after application of a tourniquet. Three times blood sample was collected, and coagulation parameters were recorded and compared. The first sample was collected at the time of TXA injection and application of a tourniquet, second after 4 hours and third after 24 hours post TXA injection. Coagulation parameters noted were analyzed using Statistical analysis by SPSS software. All parameters were compared in relation to baseline i.e. at the time of TXA injection. Results: On comparison of demographic profile, morbidity, sofa score and hemodynamic parameters there was the insignificant difference (P > 0.05). Repeated measures of ANOVA at 95% Confidential Interval P value was 0.000 which is less than the significant level that is 0.05 so that value of Platelet Function (PF), Activated Coagulation Time (ACT) and Clot Rate (CR) at 0 hrs, 04 hrs and 24 hrs was statistically significant. Correlation between blood loss and difference of the value of ACT at 0 hrs and 04 hrs is a small negative correlation but statistically nonsignificant (P value is 0.359). Conclusions: After TXA administration there is a change in coagulation parameters like an Activated Coagulation Time (ACT), Platelet Function (PF), and Clot Rate (CR) measured at three intervals, hence it can be a guide to detect early derangement in the coagulation profile in a patient undergoing knee replace surgery. TXA correlation between blood loss with changes in parameters of coagulation i.e. ACT, PF and CR were noted but not significant.